1979
DOI: 10.1227/00006123-197902000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological Assessment of Spinal Circuits in Spasticity by Direct Dorsal Root Stimulation

Abstract: Experimental researchers have shown that, because of normal inhibitory processes, repetitive orthodromic stimulation of the dorsal spinal roots induces a depression of the reflex discharge in the spinal motoneurons that is a function of the stimulation rate. Because a lack of inhibitory processes is considered to be the basic mechanism of spasticity, intraoperative stimulation of dorsal spinal roots from L-1 to S-1 bilaterally was performed in 80 patients affected by cerebral palsy. In these patients spasticit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

1994
1994
2001
2001

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 82 publications
(20 citation statements)
references
References 0 publications
0
20
0
Order By: Relevance
“…In the 1970s, Fasano et al [5, 19]described selective posterior rhizotomy based on electromyographic responses to repetitive electrical stimulation. This technique was based on animal work which showed that monosynaptic reflex responses become progressively depressed by rapidly repeated stimulation of afferent fibers [20, 21, 22].…”
Section: The History Of Rhizotomy For the Treatment Of Spasticitymentioning
confidence: 99%
See 4 more Smart Citations
“…In the 1970s, Fasano et al [5, 19]described selective posterior rhizotomy based on electromyographic responses to repetitive electrical stimulation. This technique was based on animal work which showed that monosynaptic reflex responses become progressively depressed by rapidly repeated stimulation of afferent fibers [20, 21, 22].…”
Section: The History Of Rhizotomy For the Treatment Of Spasticitymentioning
confidence: 99%
“…The depression was thought to be due to presynaptic inhibition. Fasano et al [19]stimulated lumbosacral posterior nerve rootlets at the level of the conus medullaris in spastic children at increasing frequencies and recorded the responses from anterior roots and muscles. Stimulation at certain rootlets was associated with what was felt to be an inhibitory response, whereas others lacked the features of inhibition or were associated with exaggerated motor responses such as sustained discharges or spread of contraction to other muscle groups.…”
Section: The History Of Rhizotomy For the Treatment Of Spasticitymentioning
confidence: 99%
See 3 more Smart Citations